2016
DOI: 10.1071/an14879
|View full text |Cite
|
Sign up to set email alerts
|

Growth, feed intake and carcass characteristics of indigenous goats fed local resources in Tunisian arid land

Abstract: Native genetic resource of goats is a pivotal source for meat and milk in southern Tunisia. Feeding is one of the most important activities of goat husbandry. Perceptions on the role of native feed resources for growth and carcass characteristics have not been well studied. Therefore, the present study was designed to help understand and to compare the influences of local forage resources (grass hay, dried olive leaves, Stipa tenacissima and oat hay) on growth performance and carcass characteristics of kids. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
1
1
Order By: Relevance
“…Coulon and Priolo (2005) suggested that the effect of diet on the sensory profile of meat, in particular in colour change, could be, partly, due to a change in ultimate pH, but also the age at slaughter, the carcasses fatness and the intramuscular fat content contributed to colour and tenderness changes of the meat. This is not the case in the present study since the kids were slaughtered at the same age, and intramuscular fat content was similar in the three groups (Ayeb et al, 2015). The majority of the evidence suggests that there is little or no effect of pre-slaughter growth rate on meat tenderness ( Note: C, Oat hay; CLA, conjugated linoleic acid; Ko, Khortane; MUFA, monounsaturated fatty acids; OL, Stipa tenacissima + dried olive leaves; p, probability; P/S, polyunsaturated/Saturated fatty acids; PUFA, polyunsaturated fatty acids; SEM, standard error of the means; SFA, saturated fatty acids; ΣC18:1t-11t, sum of C18:1 t-6 to t-16 excluded C18:1 t-11; ΣC18:1c-9c, sum of C18:1 cis excluded C18:1 9c; ΣCLA, sum of conjugate linoleic acids.…”
Section: Sensory Analysiscontrasting
confidence: 52%
See 1 more Smart Citation
“…Coulon and Priolo (2005) suggested that the effect of diet on the sensory profile of meat, in particular in colour change, could be, partly, due to a change in ultimate pH, but also the age at slaughter, the carcasses fatness and the intramuscular fat content contributed to colour and tenderness changes of the meat. This is not the case in the present study since the kids were slaughtered at the same age, and intramuscular fat content was similar in the three groups (Ayeb et al, 2015). The majority of the evidence suggests that there is little or no effect of pre-slaughter growth rate on meat tenderness ( Note: C, Oat hay; CLA, conjugated linoleic acid; Ko, Khortane; MUFA, monounsaturated fatty acids; OL, Stipa tenacissima + dried olive leaves; p, probability; P/S, polyunsaturated/Saturated fatty acids; PUFA, polyunsaturated fatty acids; SEM, standard error of the means; SFA, saturated fatty acids; ΣC18:1t-11t, sum of C18:1 t-6 to t-16 excluded C18:1 t-11; ΣC18:1c-9c, sum of C18:1 cis excluded C18:1 9c; ΣCLA, sum of conjugate linoleic acids.…”
Section: Sensory Analysiscontrasting
confidence: 52%
“…Coulon and Priolo () suggested that the effect of diet on the sensory profile of meat, in particular in colour change, could be, partly, due to a change in ultimate pH, but also the age at slaughter, the carcasses fatness and the intramuscular fat content contributed to colour and tenderness changes of the meat. This is not the case in the present study since the kids were slaughtered at the same age, and intramuscular fat content was similar in the three groups (Ayeb et al, ). The majority of the evidence suggests that there is little or no effect of pre‐slaughter growth rate on meat tenderness (Perry & Thompson, ), and the relationship may however depend on the cooking method that is used.…”
Section: Discussionmentioning
confidence: 48%
“…This could be justi ed by the fact that goats with indigenous bloods are adapted well in the local climatic conditions and well used to consume local forages. A similar observation was reported in a Tunisia arid land where indigenous goats could increase the intake of local forage and thus increase carcass weight (Ayeb et al, 2016).…”
Section: Nutrient Intakes and Feed Conversion Ratiosupporting
confidence: 84%